Pendekatan Konseling Gestalt Untuk Pemulihan Adiksi NAPZA Pada Remaja - Septiani, Lisa; Anwar, Marissa Nabila Putri; Amalda; Nabila Yahya, Khairunisha; Fajariyah, Syafa'atun Nur; Maulidiyah, Nuris Sa'idah Rahmah; Nuryono, Wiryo; Ratnasari, Devi (Universitas Palangka Raya, 2025)
The abuse of Narcotics, Psychotropics, and other Addictive Substances (NAPZA) among adolescents continues to rise despite widespread awareness of its dangers. Environmental factors, social pressure, and lack of self-awareness are key contributors. This study aims to examine the Gestalt counseling approach as an intervention method for NAPZA addicts to enhance their self-awareness. The research employs a literature review method by analyzing various journals, books, and documents discussing NAPZA addiction and the application of Gestalt counseling in addiction rehabilitation. The findings indicate that the primary causes of NAPZA addiction include sensation-seeking, escaping from problems, and social influences such as Fear of Missing Out (FOMO). The impact of addiction extends to physical, psychological, and social disturbances. Gestalt counseling, which emphasizes self-awareness and personal responsibility, has proven effective in helping addicts recognize emotions, accept themselves, and make healthier decisions. Techniques such as the empty chair dialogue and responsibility exercises assist addicts in addressing internal conflicts and developing a better understanding of themselves. In conclusion, the Gestalt approach can be an effective method for addressing NAPZA addiction, particularly in enhancing self-awareness and individual responsibility. Future research is recommended to explore the effectiveness of this method in different cultural and rehabilitation contexts.